Climate change and phenological responses of two seabird species breeding in the high-Arctic - Moe, Borge; Stempniewicz, Lech; Jakubas, Dariusz; Angelier, Frédéric; Chastel, Olivier; Dinessen, Frode; Gabrielsen, Geir Wing; Hanssen, Frank; Karnovsky, Nina J.; Ronning, Bernt; Welcker, Jorg; Wojczulanis-Jakubas, Katarzyna; et al. (Marine Ecology Progress Series, 2009)
International audience The timing of breeding is a life-history trait that can greatly affect fitness, because successful reproduction depends on the match between the food requirements for raising young and the seasonal peak in food availability. We analysed phenology (hatch dates) in relation to climate change for 2 seabird species breeding in the high-Arctic, little auks Alle alle and black-legged kittiwakes Rissa tridactyla, for the periods 1963–2008 and 1970–2008, respectively. We show that spring climate has changed during the study period, with a strong increase in both air temperature (TEMP) and sea surface temperature (SST) and a decrease in sea ice concentration. Little auks showed a trend for earlier breeding over the study period, while kittiwakes showed a non-significant trend for later breeding, demonstrating different phenological responses in these 2 species. Little auks and kittiwakes adjusted their timing of breeding to different environmental signals. Spring TEMP was the best predictor of little auk phenology, with a significant negative effect. Spring SST was the strongest predictor of kittiwake phenology, with a non-significant negative effect. Spring sea ice concentration and the North Atlantic Oscillation (NAO) winter index had a low relative variable importance. Furthermore, in kittiwakes, years with late breeding were associated with low clutch size and mean annual breeding success, indicating poor investment and food availability. This study identifies some spring environmental factors important for regulating the timing of breeding in the high-Arctic, most likely through effects on snow cover limiting access to nest sites and the development of the polar marine food web. It remains to be investigated whether environmental factors are reliable predictors of marine prey phenology, and whether the decision to start breeding is constrained by food availability.